American exceptionalism and policies against terrorism under bush and Obama administration = Chủ nghĩa ngoại lệ Mỹ và chính sách chống khủng bố dưới nhiệm kỳ của tổng thống Bush và Obama - Nguyễn, Ngọc Anh (2021)
Due to its different interpretations, the concept American Exceptionalism has given rise to a number of debates among scholars. It is also supposed that an insight into the term can help justify the policies enacted by the political leaders. Inspired by this idea, this paper investigates the perception of the two latest US presidents, George W. Bush and Barack Obama on the concept and how it influenced their decision on the strategies against terrorism, which is a burning issue globally. The study employed content analysis with much consideration given to data selection. After careful consideration, the speeches of the two Presidents that include explicit rhetoric on the term, their inaugurations and the annual addresses to the Congress were chosen to analyze. Besides, a wide range of articles and studies were selected as a reliable resource of the study. The findings reveal that both Presidents showed their firm support for American Exceptionalism though the way they defined it varies tremendously. While Bush was proud of the country’s betterness and advancement with a God-given mission to enlighten the world, Obama defined the uniqueness as the indispensable leading role of America in cooperation with other countries. This led to the difference in the way the two presidents justified their strategies against terror which surprisingly bear a strong resemblance